Future Directions of Legal Harmonisation and Law Reform : Stormy Seas or Prosperous Voyage ? - Faria, José Angelo Estrella (Uniform Law Review, 2009)

The need to harmonise trade-related laws within countries of the African Union: an introduction to the problems posed by legal divergence - Dlagnekova, Polina (Fundamina : A Journal of Legal History, 2009)
It is widely accepted that inter-state relationships have entered an era of globalisation. The economic theory of convergence explains that it is this phenomenon which has spearheaded, amongst others, the development of international rules in the field of trade, finance and taxation.

Unified Business Laws for Africa: Common Law Perspectives on OHADA - Dickerson, Claire Moore (GMB Publishing Ltd, 2009)